Tumour‐associated macrophages might represent a favourable prognostic indicator in patients with papillary renal cell carcinoma. Issue 3 (26th June 2013) - Hutterer, Georg C; Pichler, Martin; Chromecki, Thomas F; Strini, Karin A; Klatte, Tobias; Pummer, Karl; Remzi, Mesut; Mannweiler, Sebastian; Zigeuner, Richard
<x xml:space="preserve">Abstract</x> Aims Tumour‐associated macrophages (TAM) have been reported to be regulators of progression in various human cancers. We evaluated the prognostic relevance of TAM in a large series of patients with papillary renal cell carcinoma (PRCC). Methods and results The impact of TAM on cancer‐specific survival (CSS) in 177 patients with PRCC was assessed using the Kaplan–Meier method and log‐rank test. A multivariate Cox regression analysis was performed with respect to CSS. The presence of TAM was noted in 112 of 177 (63%) tumours and was associated statistically significantly with favourable pathological parameters, including low pathological T stage, node‐negative tumours, low tumour grade, absence of vascular invasion and papillary subtype (all P < 0.05), respectively. Five‐year CSS probabilities for patients with TAM‐positive tumours were 93.5%, compared with 72.5% in patients with TAM‐negative tumours, respectively (P < 0.001). Multivariate analysis revealed node‐positive tumours, distant metastases and UICC stage (I versus II–IV) as independent predictors of death from PRCC, whereas the presence of TAM was associated independently with favourable outcome (hazard ratio = 0.45, 95% confidence interval 0.24–0.84, P = 0.012). Conclusions The presence of TAM was shown independently to reduce the risk of death from cancer by 55%. The presence of TAM should therefore become part of routine pathology reporting in PRCC.